The Radiologist’s Role in Supporting Patients with Chronic Conditions: A Literature Review - Radi Lafi Alharbi , Mamdouh Nasser Alharbi , ‏Naif Maleh Alharbi , Saleh Sanat Alharbi , Abdulmajeed Bain Alharbi , Dhari Qaed Alharbi , Ahmad Naif Alharbi , Yousef Ghazi Alrashidi , Sultan Falah Alharbi (Migration Letters, 2022)
Background: Chronic conditions, such as cardiovascular diseases, diabetes, cancer, and chronic respiratory disorders, pose significant challenges to global health systems. Radiologists play a pivotal role in the diagnosis, monitoring, and treatment of these conditions, leveraging advanced imaging technologies to enhance patient care. Objective: This literature review aims to synthesize current research on the contributions of radiology to the management of chronic diseases, emphasizing diagnostic accuracy, disease progression monitoring, therapeutic planning, and patient outcomes. Methods: A systematic search of PubMed, Scopus, Web of Science, and Cochrane Library databases was conducted, focusing on studies published in English between January 2010 and December 2023. The search strategy included terms related to radiology, chronic conditions, and patient care. Studies were selected based on predefined inclusion and exclusion criteria, with data extracted on study design, radiological modalities, and outcomes. Results: The review included 16 studies, highlighting the crucial role of radiology in early disease detection, accurate diagnosis, and the monitoring of disease progression. Interventional radiology was shown to contribute significantly to minimally invasive treatments, improving patient quality of life. Despite these advancements, challenges such as access disparities and the ethical implications of overdiagnosis were identified. Conclusions: Radiology significantly impacts the management of chronic conditions, offering invaluable tools for diagnosis, treatment, and patient care optimization. Future research should address existing gaps, including standardized imaging protocols and the integration of artificial intelligence, to further enhance the role of radiology in chronic disease management.